Sinusoidally Modulated Silicon Leaky Wave Antenna for sub-THz Applications - B. M. Yousef; A. M. Ameen; A. M. Attiya; A. A. Shaalan (Advanced Electromagnetics, 2019)
A new sub-THz leaky wave antenna based on grounded silicon substrate for chip to chip communication applications is presented. The proposed leaky wave antenna is based on sinusoidally modulated surface reactance. This surface reactance is implemented by using varying width strips on the top of a grounded silicon substrate. Two approaches for developing these strips are studied. These two approaches are based on either highly doped silicon strips or gold strips. Both the doped silicon and the gold are presented by using their corresponding Drude models at the proposed operating frequency. Comparisons between the properties of these two approaches are presented to show the applicability of each one.